2020
DOI: 10.15403/jgld-562
|View full text |Cite
|
Sign up to set email alerts
|

International Consensus on Diverticulosis and Diverticular Disease. Statements from the 3rd International Symposium on Diverticular Disease

Abstract: The statements produced by the Chairmen and Speakers of the 3rd International Symposium on Diverticular Disease, held in Madrid on April 11th-13th 2019, are reported. Topics such as current and evolving concepts on the pathogenesis, the course of the disease, the news in diagnosing, hot topics in medical and surgical treatments, and finally, critical issues on the disease were reviewed by the Chairmen who proposed 39 statements graded according to level of evidence and strength of recommendation. Each topic wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 76 publications
(89 reference statements)
0
61
1
6
Order By: Relevance
“…11 As a consequence, the current guidelines identify SUDD as a distinct clinical syndrome. 12 Acute diverticulitis The term "acute diverticulitis" describes the macroscopic inflammation of diverticula. The condition can be uncomplicated or complicated.…”
Section: Symptomatic Uncomplicated Diverticular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…11 As a consequence, the current guidelines identify SUDD as a distinct clinical syndrome. 12 Acute diverticulitis The term "acute diverticulitis" describes the macroscopic inflammation of diverticula. The condition can be uncomplicated or complicated.…”
Section: Symptomatic Uncomplicated Diverticular Diseasementioning
confidence: 99%
“…colonic wall thickening with fat stranding, while it is complicated when CT detects features of inflammatory complications (abscess, peritonitis, obstruction, fistulas). 12 The management of acute diverticulitis is associated with significant direct and indirect costs for national health systems. 13 Even if the disease seems to occur less frequently than previously estimated, 14 it has been shown to relapse more frequently.…”
mentioning
confidence: 99%
“…Some studies tried to show that these are flaw evidences, since patients having diverticulosis and chronic abdominal symptoms do not show any evidence of inflammation [9]. However, the definition of "abdominal chronic symptoms in diverticulosis" does not fulfil the current definition of SUDD [46]. On the contrary, patients fulfilling the correct definition of SUDD show all the reported evidences on the role of inflammation in the pathogenesis of SUDD [47].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…Recent studies demonstrated that DD is associated with peculiar alterations of the enteric nervous system (ENS), encompassing myenteric oligoneuronal hypoganglionosis, decreased intramuscular nerve fibers, and altered neurochemical coding [40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Analyzing the expression of the glial markers S100β, Cossais et al found very recently that S100β expression was increased in the submucosal and myenteric plexus of patients with DD compared with that in controls, whereas the expression of other glial factors remained unchanged.…”
Section: Relationship Between Low-grade Inflammation and Other Mechanmentioning
confidence: 99%
See 1 more Smart Citation